2009
DOI: 10.1161/circheartfailure.108.801548
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Vasodilators in an Animal Model of Chronic Volume Overload Caused by Severe Aortic Regurgitation

Abstract: Background-Aortic regurgitation (AR) is a disease of chronic left ventricular (LV) volume overload. Over time, AR will lead to LV dilatation, hypertrophy, and loss of function. There is currently no medical treatment proven effective to slow the evolution of this cardiomyopathy. Vasodilators were once thought to have protective effects, but recent publications have cast some doubts about their effectiveness. We hypothesized that drugs targeting the renin-angiotensin system should be more effective than those h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…A 7-month follow-up may reflect the subacute period in humans, and it does enclose a true chronic phase in rats because we have previously shown in a paper characterizing this animal model. 6,8 Our results show a clear effect on LV dilatation, hypertrophy, systolic function, myocardial metabolism, and more importantly on survival. These results provide support for the need to reevaluate ACEI in humans with AR in a large prospective clinical trial.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…A 7-month follow-up may reflect the subacute period in humans, and it does enclose a true chronic phase in rats because we have previously shown in a paper characterizing this animal model. 6,8 Our results show a clear effect on LV dilatation, hypertrophy, systolic function, myocardial metabolism, and more importantly on survival. These results provide support for the need to reevaluate ACEI in humans with AR in a large prospective clinical trial.…”
Section: Discussionmentioning
confidence: 54%
“…We previously showed that blood pressure in AR animals treated with Cpt is only slightly reduced and had similar findings in this protocol. 6 This suggests that the hemodynamic contribution to the benefits of angiotensin-converting enzyme (ACE) inhibition although present is not the main and only factor involved. 6 The previously reported shift toward glucose use by the myocardium in compensated hypertrophy was not observed in our Cpt-treated AR rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…53 Correspondingly, ARBs have paved a promising path in the treatment of VO cardiac hypertrophy. 46, 54 The widespread experimental findings and clinical applications of ARBs to ameliorate cardiac remodeling under PO and VO are testament to the importance of the AT1-R. Yet, questions remain.…”
Section: Downstream Signaling Pathways Of the At1-rmentioning
confidence: 99%